Acclimatization of Cultivated Plants on the Northern Limit of Agriculture in the USSR - Stanek, Ph.D., Zofia (ARCTIC, 1970)
These studies on the acclimatization of cultivated plants at the northern limit of agriculture in the USSR are based on observations and experiments that were completed in the northern part of the Krasnoyarski Kray, a region of Siberia, from 1951 to 1957, and supplemented with data from the literature concerning agriculture in the Far North. The term northern limit of agriculture has variable meaning. It is a line on the map drawn through the most northerly points where plants are still cultivated in the open or under glass. These places are often separated by thousands of square kilometres of taiga, peat bogs and sparse forests on the edge of the tundra, because the only places of habitation are along the largest Siberian rivers. The main experimental stations are: Archangel on the Dvina, Nary'an Mar on the Pechora, Salekhard on the Ob', Igarka on the Yenisey, Tiksi on the delta of the Lena, Vekhoyansk on the Yana, Nizhne Kolymsk on the Kolyma, Markovo on the Anadyr. . Conclusion: The main problems of northern agriculture are: 1) The reaction of plants to the short vegetative period and to the long polar day; 2) The influence of permafrost on the soil and on plant life. Proper methods of cultivating and manuring help to surmount these difficulties and to develop to some extent the production of vegetables for the use of people living in the Arctic. Vegetable production in the Far North is at the moment only of strictly local importance, but the populated regions of the Arctic are growing as a consequence of scientific and technical progress. Electrification, aeronautics and radio were factors which improved the living conditions of people in the North. Mining provided a basis for the development of industry. Agriculture and cattle breeding followed industry to ensure adequate food supplies when transport from the south was difficult. These new methods of plant culture have opened up new horizons in the Far North not only in Russia, but also in Canada and in the Arctic Islands. Northern agriculture in its ...